2021
DOI: 10.1111/gcb.15923
|View full text |Cite
|
Sign up to set email alerts
|

Testing the match–mismatch hypothesis in bighorn sheep in the context of climate change

Abstract: Climate change is expected to shift both the timing and duration of vegetation growth in temperate environments (Thackeray et al., 2010). Facing these changes, wild animals can modify their reproductive phenology to track vegetation availability (Parmesan, 2006;Walther et al., 2002) and match the greatest reproductive expenditure with the best food conditions, but only if cues for anticipated environmental conditions remain reliable. Mismatch refers to the desynchronized timing of critical events between inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…It can be difficult to know how far back to look for climate predictors of an organism's phenology. Some cues can prompt responses within a day, such as plants flowering immediately post-snowmelt [85,86], other cues prompt responses within a month or two, such as warm spring weather stimulating insect emergence [39,87], and still other responses occur across seasons, such as fall temperature determining conception timing, and thus spring birth of arctic ungulates [44,[47][48][49]. Cues can also accumulate over time and interact with organisms' physiological demands; for example, a warm winter combined with a warm spring delays first flower of some plant species, because they have not met their vernalization-chilling requirements [88,89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be difficult to know how far back to look for climate predictors of an organism's phenology. Some cues can prompt responses within a day, such as plants flowering immediately post-snowmelt [85,86], other cues prompt responses within a month or two, such as warm spring weather stimulating insect emergence [39,87], and still other responses occur across seasons, such as fall temperature determining conception timing, and thus spring birth of arctic ungulates [44,[47][48][49]. Cues can also accumulate over time and interact with organisms' physiological demands; for example, a warm winter combined with a warm spring delays first flower of some plant species, because they have not met their vernalization-chilling requirements [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…This timeframe can range from weeks to years prior to a given phenological event [43][44][45][46]. Prior weather can be a good phenological predictor, such as in Arctic ungulates where fall temperature determines conception timing and thus spring parturition date [44,[47][48][49]. Fall weather can also predict flowering times for fruit trees and other angiosperms in the following spring [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have attempted to estimate effects of past and future climate variation on bighorn sheep, including both native and restored populations (Epps et al, 2004;Colchero et al, 2009). Nonetheless, a study investigating temporal mismatch between vegetation green-up and parturition date in Rocky Mountain bighorn sheep, an expected consequence of climate change, concluded that mismatch did not have major consequences for fitness (Renaud et al, 2022).…”
Section: Climate Change and Future Habitat Conditionsmentioning
confidence: 99%